Peran Teknologi Informasi dalam Meningkatkan Efektivitas Program Corporate Social Responsibility (CSR) Pada Yayasan XYZ - Azhari, Ozmar; Anwar, Sahrul; Lee, Francka Sakti; Honni, Honni (Universitas Bunda Mulia, 2025)
Information Technology (IT) has become an essential element of human activity, including the implementation of Corporate Social Responsibility (CSR) programs aimed at community empowerment. One organization conducting such programs is Foundation XXX, a non-profit focused on education that routinely carries out CSR initiatives in partnership with various stakeholders. This study seeks to evaluate the effectiveness of IT-based partnerships within the foundation’s CSR program. A qualitative approach was employed through in-depth interviews with stakeholders, field observations, document analysis, and a literature review. Findings indicate that using online communication platformsm such as Zoom and Google Meet, and digital monitoring systems enhances inter-party coordination, transparency in resource allocation, and community participation. IT also facilitates real-time progress tracking, enabling faster, data-driven decision-making. Nonetheless, challenges such as digital-literacy gaps, infrastructure limitations, and incomplete system integration still hinder optimal benefits. The research underscores the need for a comprehensive IT strategy encompassing literacy training, platform standardization, and a sustainable integration plan to maximize CSR impact. These findings are expected to guide similar organizations in designing IT-based CSR initiatives that are sustainable and results-oriented. Practical implications include formulating supportive policies and fostering multi-party collaboration to bridge technological gaps and ensure equitable benefits for all stakeholders within the organization